Electrical stimulation accelerates Wallerian degeneration and promotes nerve regeneration after sciatic nerve injury. Issue 3 (9th December 2022) - Li, Xiangling; Zhang, Tieyuan; Li, Chaochao; Xu, Wenjing; Guan, Yanjun; Li, Xiaoya; Cheng, Haofeng; Chen, Shengfeng; Yang, Boyao; Liu, Yuli; Ren, Zhiqi; Song, Xiangyu; et al.
Abstract: Following peripheral nerve injury (PNI), Wallerian degeneration (WD) in the distal stump can generate a microenvironment favorable for nerve regeneration. Brief low‐frequency electrical stimulation (ES) is an effective treatment for PNI, but the mechanism underlying its effect on WD remains unclear. Therefore, we hypothesized that ES could enhance nerve regeneration by accelerating WD. To verify this hypothesis, we used a rat model of sciatic nerve transection and provided ES at the distal stump of the injured nerve. The injured nerve was then evaluated after 1, 4, 7, 14 and 21 days post injury (dpi). The results showed that ES significantly promoted the degeneration and clearance of axons and myelin, and the dedifferentiation of Schwann cells. It upregulated the expression of BDNF and NGF and increased the number of monocytes and macrophages. Through transcriptome sequencing, we systematically investigated the effect of ES on the molecular processes involved in WD at 4 dpi. Evaluation of nerves bridged using silicone tubing after transection showed that ES accelerated early axonal and vascular regeneration while delaying gastrocnemius atrophy. These results demonstrate that ES promotes nerve regeneration by accelerating WD and upregulating the expression of neurotrophic factors. Main Points: Electrical stimulation (ES) accelerates Wallerian degeneration after peripheral nerve injury. ES promotes early axonal and vascular regeneration while delays gastrocnemius atrophy.